2022
DOI: 10.1111/nuf.12735
|View full text |Cite
|
Sign up to set email alerts
|

Physical problems of prolonged use of personal protective equipment during the COVID‐19 pandemic: A scoping review

Abstract: Background It is widely believed that using personal protective equipment (PPE) provides high levels of protection for healthcare workers (HCWs) in the fight against coronavirus disease (COVID‐19). However, the long‐term use of PPE is inconvenient for HCWs and may cause physical discomfort. These factors could result in poor compliance and disrupt the health and safety of HCWs, which may negatively affect the patient's safety. Objective This study aimed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
(187 reference statements)
1
14
0
Order By: Relevance
“…41 It has also been found in previous studies that while protective gear reduces the risk of infection for medical personnel, a variety of physical health problems can occur, including skin, respiratory, musculoskeletal, neurological, urinary, and circulatory problems, with skin problems being the most common. 42 These findings are consistent with those of previous studies on the spread of severe acute respiratory syndrome (SARS). 43 Long-term use of the facial protective gear is associated with a high rate of adverse skin reactions.…”
Section: Discussionsupporting
confidence: 92%
“…41 It has also been found in previous studies that while protective gear reduces the risk of infection for medical personnel, a variety of physical health problems can occur, including skin, respiratory, musculoskeletal, neurological, urinary, and circulatory problems, with skin problems being the most common. 42 These findings are consistent with those of previous studies on the spread of severe acute respiratory syndrome (SARS). 43 Long-term use of the facial protective gear is associated with a high rate of adverse skin reactions.…”
Section: Discussionsupporting
confidence: 92%
“…This mixed-methods study addressed the impact of caring for hospitalized COVID-19 patients on both the physical and mental health of nurses, whereas the majority of prior studies focused only on nurses’ mental health ( Chutiyami et al, 2021 ; Feingold et al, 2021 ; Giorgi et al, 2020 ; Gordon et al, 2021 ; Grailey et al, 2021 ; Joo & Liu, 2021 ; Ness et al, 2021 ; Peccoralo et al., 2022 ; Preti et al., 2020 ; Shah et al., 2021 ). Furthermore, studies that examined the impact on physical health focused on specific symptoms (e.g., headaches, fever, cough, insomnia) or adverse events secondary to PPE use (e.g., skin breakdown) rather than general health using a standardized health assessment tool such as the SF-12 ( Chew et al, 2020 ; Chutiyami et al, 2021 ; Galanis et al, 2021a ; Häussl et al., 2021 ; Manookian et al, 2022 ; Namikawa et al, 2021 ; Shaukat et al, 2020 ). Furthermore, this study revealed significant declines in general health and role performance from physical and mental health problems heretofore not addressed in previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses reported skin breakdown, dehydration, and skin infections from PPE use. Adverse effects on physical health secondary to PPE use reported by others include pressure injuries, dermatitis, dehydration, and headaches ( Galanis et al, 2021a ; Manookian et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations